2014
DOI: 10.1155/2014/769732
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Water Stress on Some Morphological, Physiological, and Biochemical Characteristics and Bud Success on Apple and Quince Rootstocks

Abstract: The effects of different water stress (control, medium, and severe) on some morphological, physiological, and biochemical characteristics and bud success of M9 apple and MA quince rootstocks were determined. The results showed that water stress significantly affected most morphological, physiological, and biochemical characteristics as well as budding success on the both rootstocks. The increasing water stress decreased the relative shoot length, diameter, and plant total fresh and dry weights. Leaf relative w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
61
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 24 publications
10
61
1
2
Order By: Relevance
“…Reduced water availability results in limited cell division due to impaired mitosis and obstructed cell elongation due to loss of turgor that ultimately diminishes growth (Farooq et al 2009). Water deficit influences most of the morphological and physiological traits of host plants such as plant height, diameter, growth, plant total fresh and dry weight, and leaf water content (Zhang et al 2009;Bolat et al 2014), depending on the host plant species, and the level, duration and type of stress (Mattson and Haack 1987;Grime and Compbell 1991). In the present study, both host plants showed reduced leaf water potential under water-deficit conditions.…”
Section: Discussionsupporting
confidence: 48%
“…Reduced water availability results in limited cell division due to impaired mitosis and obstructed cell elongation due to loss of turgor that ultimately diminishes growth (Farooq et al 2009). Water deficit influences most of the morphological and physiological traits of host plants such as plant height, diameter, growth, plant total fresh and dry weight, and leaf water content (Zhang et al 2009;Bolat et al 2014), depending on the host plant species, and the level, duration and type of stress (Mattson and Haack 1987;Grime and Compbell 1991). In the present study, both host plants showed reduced leaf water potential under water-deficit conditions.…”
Section: Discussionsupporting
confidence: 48%
“…Similar results were reported by Sauve et al (1991) for Golden Delicious/M111 budding combination, which was severely affected in pre and post chip budding in −5 to −25 kPa water stress applications. Bolat et al (2014) reported that chip budding success was gradually reduced in Vista Bella apple/M9 apple rootstock and Santa Maria pear/MA quince rootstocks combinations under gradual increase of water stress.…”
Section: Resultsmentioning
confidence: 99%
“…4) Our results concords with those from the scientific literature that signalize a strong ROS accumulation and, implicitly, a CAT activity's increase at species derived from uranium polluted environments 55 . In the same time, the prominent differences of enzymatic activity could be explain by the seasonal variations, but also zonals, of the hydric level, the hydric regime potencying the forming process of the superoxidic radical, fact that has as consequence a sustained SOD activity and, implicitly, of CAT that block the hydrogen peroxide accumulation 56,57 . On the other hand, the lower catalasic activity signalized at Mentha longifolia L., comparatively with Plantago major L., can be explained by the genetic background and the species specificity, but also by the epigenetic adjustment through the interaction with environmental factors 58 .…”
Section: Resultsmentioning
confidence: 99%